(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to Eastern poetry, especially to German romantic literature of Persian classic literature, to open effective influence to Goytе and Hayne creative works as well as it shows different treats about destiny of Abulkasim Firdausi in great German creative works